Способ прогнозирования износостойкости твердосплавных режущих инструментов - Нестеренко В. П. Владимир Петрович; Арефьев К. П. Константин Петрович; Кондратюк А. А. Алексей Алексеевич; Меркулов В. И. Валерий Иванович; Романов Б. П.; Суржиков А. П. Анатолий Петрович
опубл. 27.07.03